1983
DOI: 10.1037/0022-0167.30.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Influence of career indecision on treatments exploring the vocational interests of college women.

Abstract: This study randomly assigned undergraduate women at each of three levels of career indecision to a Vocational Card Sort treatment group, a Strong-Campbell Interest Inventory treatment group, or a no-treatment control group. A total of 180 women (20 per cell) voluntarily participated. Career indecision was measured by the Occupational Alternatives Question. A variety of outcome measures were used including items measuring the vocational needs of subjects, the Vocational Exploration Behavior Checklist, the Satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…The OAQ is scored as follows : 1 = a first choice is listed with no alternatives, 2 = a first choice is listed with alternatives, 3 = no first choice is listed, just alternatives, and 4 = neither is listed. Using this scoring procedure, the concurrent validity of the OAQ with other measures of career indecision has been demonstrated in several studies (Slaney, 1980(Slaney, , 1983Slaney, Stafford, & Russell, 1981). Test-retest reliability was reported at .93 (Redmond, 1973) and found to be stable over a six week period (Slaney, 1978).…”
Section: Methodsmentioning
confidence: 91%
“…The OAQ is scored as follows : 1 = a first choice is listed with no alternatives, 2 = a first choice is listed with alternatives, 3 = no first choice is listed, just alternatives, and 4 = neither is listed. Using this scoring procedure, the concurrent validity of the OAQ with other measures of career indecision has been demonstrated in several studies (Slaney, 1980(Slaney, , 1983Slaney, Stafford, & Russell, 1981). Test-retest reliability was reported at .93 (Redmond, 1973) and found to be stable over a six week period (Slaney, 1978).…”
Section: Methodsmentioning
confidence: 91%
“…The test-retest reliability correlation of a questionnaire that included this question was .93 (Redmond, 1973). Three studies (Slaney, 1980(Slaney, , 1983Slaney et al, 1981) demonstrated considerable support for the concurrent validity of the OAQ with other measures of career indecision when the responses were scored as follows: 1 = a first choice is listed with no alternatives, 2 = a first choice is listed with alternatives, 3 = no first choice is listed, just alternatives, and 4 = neither is listed. This scoring system was used in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…A few measures, fortunately, appear to be quite good. The VDMD scale (Holland & Holland, 1977) and the use of the OAQ (Slaney, 1980(Slaney, , 1983 also appear to be quite beneficial to career indecision research. The VDMD scale (Holland & Holland, 1977) and the use of the OAQ (Slaney, 1980(Slaney, , 1983 also appear to be quite beneficial to career indecision research.…”
Section: Summary and Recommendationsmentioning
confidence: 99%